2021
DOI: 10.1002/cssc.202100761
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted Charge Transfer Between DMF and Substrate: Facile and Selective N,N‐Dimethylamination of Fluoroarenes

Abstract: A reversible Van der Waals complex formation between the electron‐deficient fluorinated aromatic ring and N,N‐dimethylformamide (DMF) molecules followed by light irradiation resulted in charge transfer (CT) process. The complex was stabilized by ammonium formate and further decomposed to form the C−N bond. Control experiments revealed that the simultaneous SNAr pathway also contributes to product formation. This methodology is mild, metal‐free, and effective for the amination of a variety of substrates. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The subsequent decomposition leads to ArNMe 2 or ArF and HNMe 2 . The S N Ar reaction between the two latter species could also contribute to the product formation [37]. Under the optimum conditions, switching the solvent of the reaction of octafluoronaphthalene from DMF to DMAc decreased the yield of 1,3,4,5,6,7,8-heptafluoro-N,N-dimethylnaphthalen-2-amine from 80% to traces.…”
Section: Aryl Halides and Tosylatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent decomposition leads to ArNMe 2 or ArF and HNMe 2 . The S N Ar reaction between the two latter species could also contribute to the product formation [37]. Under the optimum conditions, switching the solvent of the reaction of octafluoronaphthalene from DMF to DMAc decreased the yield of 1,3,4,5,6,7,8-heptafluoro-N,N-dimethylnaphthalen-2-amine from 80% to traces.…”
Section: Aryl Halides and Tosylatesmentioning
confidence: 99%
“…Recently, the Kozlowski/Handa team disclosed the dimethylamination of fluoro (hetero)arenes with DMF in the presence of ammonium formate and light (Scheme 7e) [37]. According to computational studies and control experiments, the Van der Waals complex formed from the electron-deficient fluorinated aromatic ring and DMF evolves under light toward a charge transfer complex stabilized by ammonium formate.…”
Section: Aryl Halides and Tosylatesmentioning
confidence: 99%
“…be accomplished by irradiating polyfluoroarene in the presence of ammonium formate in N,N-dimethylformamide, which acts as a source of the amine moiety. 68 Later, an alternative approach to achieve photocatalytic hydrodefluorination was reported by Fu and co-workers (Scheme 9). 69 The protocol involves stoichiometric amounts of silane in methanol/ethylene glycol mixture under light irradiation at elevated temperature by means of rhodium porphyrin catalysis.…”
Section: Polyfluoroarenes As Sources Of Aryl Radicalsmentioning
confidence: 99%
“…The formation of such complexes is typical for polyfluoroarenes 30,171 and their reactions. 63,68,172,173 Although initially the chemistry of these sulfides concerned the generation of only fluoroalkyl radicals, it turned out that non-activated sulfides can also work under photocatalytic conditions (Scheme 67). 174 Reductive cleavage of the C-S bond generates an alkyl radical, which subsequently undergoes radical addition on various trapping agents such as hetarenes, Michael acceptors, and silyl enol ethers to produce the corresponding products 67.2.…”
Section: Polyfluoroarenes As Auxiliariesmentioning
confidence: 99%
“…10 Moreover, Handa and their group described the photo-assisted cleavage of DMF for the facile and selective N , N -dimethylamination of fluoroarenes. 11 In this regard, Peng and Jin et al have demonstrated the direct amination of cyclic amides via C–OH bond activation to access heterocyclic amines in the presence of DMF (Scheme 1a). 4 In continuation of our own research on efficient and practical methodologies, 12 we report here the copper-catalyzed one-pot direct amination of cytosine amides via the activation of the C–OH bond of a carbamide (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%